Fictional dialogue and characterisation in Nelson Makuya’s short stories in A zwi faneli - Mmbulaheni L. Mudau (Literator)
This article examines the role of fictional dialogue in character development in Tshikhusese Nelson Makuya’s anthology of short stories, particularly in his 1972 collection A zwi faneli. Fictional dialogue is a vital literary device that reveals the complexities of characters’ identities, motivations and cultural backgrounds, yet it remains underexplored in African languages literature. This article analyses how dialogue functions as a literary tool for characterisation, explicitly focussing on the themes of personality traits and relationships, thereby addressing a significant gap in existing literary studies. Employing a qualitative research methodology, the article uses textual analysis to closely examine the characters’ dialogues, idiolects and interactions. It is framed within a dialogic theoretical framework, which emphasises the relational nature of identity and the dynamic evolution of characters through verbal exchanges. This framework, developed by Mikhail Bakhtin, helps understand how characters’ identities are shaped and revealed through their dialogues.